Antarctic climate, Southern Ocean circulation patterns, and deep water formation during the Eocene. (3rd July 2017) - Huck, Claire E.; van de Flierdt, Tina; Bohaty, Steven M.; Hammond, Samantha J.
Abstract: We assess early‐to‐middle Eocene seawater neodymium (Nd) isotope records from seven Southern Ocean deep‐sea drill sites to evaluate the role of Southern Ocean circulation in long‐term Cenozoic climate change. Our study sites are strategically located on either side of the Tasman Gateway and are positioned at a range of shallow (<500 m) to intermediate/deep ( 1000–2500 m) paleowater depths. Unradiogenic seawater Nd isotopic compositions, reconstructed from fish teeth at intermediate/deep Indian Ocean pelagic sites (Ocean Drilling Program (ODP) Sites 738 and 757 and Deep Sea Drilling Project (DSDP) Site 264), indicate a dominant Southern Ocean‐sourced contribution to regional deep waters ( ε Nd( t ) = −9.3 ± 1.5). IODP Site U1356 off the coast of Adélie Land, a locus of modern‐day Antarctic Bottom Water production, is identified as a site of persistent deep water formation from the early Eocene to the Oligocene. East of the Tasman Gateway an additional local source of intermediate/deep water formation is inferred at ODP Site 277 in the SW Pacific Ocean ( ε Nd( t ) = −8.7 ± 1.5). Antarctic‐proximal shelf sites (ODP Site 1171 and Site U1356) reveal a pronounced erosional event between 49 and 48 Ma, manifested by 2 ε Nd unit negative excursions in seawater chemistry toward the composition of bulk sediments at these sites. This erosional event coincides with the termination of peak global warmth following the Early Eocene Climatic Optimum and is associated with documented cooling across the study region and increased export of Antarctic deep waters, highlighting the complexity and importance of Southern Ocean circulation in the greenhouse climate of the Eocene. Key Points: Distinct neodymium water mass signature recorded in intermediate/deep waters in the SW Pacific during the Eocene Local deep water formation on Adélie Coast during Eocene greenhouse warmth A previously unidentified Antarctic erosional event occurred at 49‐48 Ma